Advertising Media, an analysis of Code in Compilation of Food and Beverage Ads on YouTube - Mulyanto, Agus; Warsiti, Sintia; Dewi, Risma Oktaviani (Journal of Pragmatics and Discourse Research, 2023)
The utilization of coding within advertising discourse is an imperative means of communication, effectively demonstrating the wide array of linguistic frameworks employed in promotional campaigns. The deliberate inclusion of diverse languages in advertisements serves the dual purpose of capturing attention and safeguarding regional languages by utilizing advertising platforms to uphold and enhance their significance. The objective of this study is to analyse instances of code switching and code mixing in compilation videos of food and beverage advertisements uploaded by Rofif Satria on the YouTube Satria Channel account.  The utilization of a qualitative methodology employing descriptive techniques in data collection entails the process of observation and subsequent documentation through note-taking. The researcher carefully examines each advertising video, meticulously documenting both the spoken and written narratives conveyed within them. The instances of code-switching and code-mixing in the compilation videos are subsequently identified, annotated, and documented. The data that has been gathered is organized and classified according to its type, as well as the specific forms of code-switching and code-mixing that are present. The research findings indicate instances of code-switching and code-mixing, which encompass both internal and external forms. These include the insertion of words, phrases, clauses, and basters. The contextualization of data, including words, phrases, and clauses, is integral to the interpretation within the discourse of advertising.